The oil and gas geologist’s Arctic in the age of the Anthropocene - knowledge, politics and imaginative geologies - Bartels, Marianne Pascale (The University of St Andrews, 2024)
This dissertation is about how geologists produce Arctic oil and gas estimate knowledge and think about what they do at a time of profound environmental and climate change (often dubbed the Anthropocene). Accordingly, the study considers how geological knowledge is produced, for what purpose and with what effects, and how geologists, chiefly in government but also in academia and industry, see themselves and their role in changing energy landscapes. Geologists are much neglected agents in contemporary energy and climate dynamics and yet are crucial to how the present and future are envisioned and represented. The originality of the study lies in its attempt to probe the geological data on Arctic oil and gas estimation and develop an insider-outsider approach to engaging with geologists that is based on a close textual examination of 23 semi-structured interviews (from a larger total of 42 conducted for the study). This involved the investigator working (‘shuttling’) between geological and geographical knowledges and approaches – trained as an industrial geologist and seeking to develop critical geographical perspectives. The thesis draws three main recognitions from the documentary and interview data, namely that: 1. Arctic oil and gas geologists perceive today as a time of unsettling change (a ‘whiplash’) and thus that their knowledge is inherently political; 2. Arctic oil and gas geologists are a much understudied and underestimated group in the story of how and why lines between Arctic ‘fossil fuel’ geologists and Arctic ‘clean energy’ geologists are becoming blurred in shifting energy landscapes (a ‘swivel’ is underway); and 3. studies like this one can add something to current debates about the power and future of oil and gas by showing the need for new interdisciplinary conversations with Arctic geologists. Finally, the thesis reflects on the student’s personal journey in translating between the worlds of geology and geography. "This work was supported by the Robertson Scholarship; and the Research ...